PROFIL PELAYANAN SWAMEDIKASI PRODUK OBAT FITOFARMAKA UNTUK PASIEN DIABETES MELITUS DI BEBERAPA APOTEK DI WILAYAH SURABAYA - AHMAD ELFARIS ASH SHIDDIQI, 051411133014 (2019)
The development of herbal research in Indonesia has increased the availability of registered herbal products. One type of the products is called phytopharmaca. The literature, however, showed that herbal medicine has been commonly used as a complement to prescribed medicines among patients with chronic diseases, including diabetes mellitus. Inappropriate use of herbal medicines in chronic conditions can be avoided if pharmacists as a medicine expertise provided relevant information to such patients. This study investigated the availability of a phytopharmaca requested for diabetes mellitus, pharmacists’ performance in assessing patient, providing recommendations and information, as well as their knowledge about phytopharmaca. A simulated-patient study was conducted in 90 randomly selected pharmacies in Surabaya. Twenty (22.2%) pharmacies provided the product requested. Only three (3.3%) pharmacy staff assessed a simulated patient. As the product requested unavailable, seven (7.7 %) pharmacy staff recommended antidiabetic synthetic medicines, while five (5.5%) suggested other herbal products in the form of “jamu”. Medicine information on dosing and time for use was only delivered in 27 (30%) pharmacies, mostly provided when requested. A third pharmacy staff correctly identified the type of herbal product requested but many of those who recommended other products were unable to provide correct answers about the difference of both products. It can be concluded that the availability of registered herbal productss for diabetes mellitus was limited. Herbal medicine usage among patients with chronic diseases may become problematic if pharmacistsor pharmacy staff have limited knowledge, with little efforts to assess patients and deliver sufficient medicine information.